Effect of sodium alginate-agar coating containing ginger essential oil on the shelf life and quality of beef. (December 2021) - Zhang, Bin; Liu, Yang; Wang, Huanhuan; Liu, Wenhua; Cheong, Kit-leong; Teng, Bo
Abstract: Edible coatings based on agar/sodium alginate (AS) and AS containing ginger essential oil (AS + GEO) were prepared and their effects on the quality and shelf-life of fresh beef during refrigerated storage studied. Uncoated (control) and coated beef samples were analyzed periodically during storage at 4 °C for microbial colony growth (total viable counts, psychrotrophs, Escherichia coli, Staphylococcus aureus, yeasts and molds), physico-chemical (thiobarbituric acid reactive substances, peroxide value), pH value, sensory evaluation, odor (electronic nose) and texture characteristics (springiness, chewiness and hardness). Coating treatments significantly ( p < 0.05) retarded the oxidation of beef slices, with TBARS values of 3.132, 1.868, 0.986 mg MDA/kg and PV values of 8.86, 7.46, 4.26 meq/kg for uncoated, AS coated and AS + GEO coated samples on day 18 of storage respectively. A similar reduction trend was observed for microbial population. TVC, PTC, E. coli, S. aureus, yeasts and molds were 7.50, 6.86, 6.20, 4.70 and 3.90 log CFU/g at the end of storage for AS + GEO coated samples lower than those of uncoated and AS coated samples. The comprehensive results from the lipid oxidation and microbial assays (especially the TVC) showed that the shelf-life for uncoated, AS coated and AS + GEO coated samples was 7 d, 10 d, 16 d, indicating the AS and AS + GEO coatings could extend the shelf life of fresh beef by 3–6 and 9 days respectively, compared with the control samples. Furthermore, the odor and texture evaluations demonstrated that the beef coated with AS + GEO had improved sensory attributes during the storage period. The results from this study may provide a basis for the development of AS + GEO as an antibacterial coating material for chilled beef storage.